Bismuth-based nanostructured photocatalysts for the remediation of antibiotics and organic dyes - Oladipo, Akeem Adeyemi; Mustafa, Faisal Suleiman (Beilstein Journal of Nanotechnology, 2023)
A serious threat to human health and the environment worldwide, in addition to the global energy crisis, is the increasing water pollution caused by micropollutants such as antibiotics and persistent organic dyes. Nanostructured semiconductors in advanced oxidation processes using photocatalysis have recently attracted a lot of interest as a promising green and sustainable wastewater treatment method for a cleaner environment. Due to their narrow bandgaps, distinctive layered structures, plasmonic, piezoelectric and ferroelectric properties, and desirable physicochemical features, bismuth-based nanostructure photocatalysts have emerged as one of the most prominent study topics compared to the commonly used semiconductors (TiO2 and ZnO). In this review, the most recent developments in the use of photocatalysts based on bismuth (e.g., BiFeO3, Bi2MoO6, BiVO4, Bi2WO6, Bi2S3) to remove dyes and antibiotics from wastewater are thoroughly covered. The creation of Z-schemes, Schottky junctions, and heterojunctions, as well as morphological modifications, doping, and other processes are highlighted regarding the fabrication of bismuth-based photocatalysts with improved photocatalytic capabilities. A discussion of general photocatalytic mechanisms is included, along with potential antibiotic and dye degradation pathways in wastewater. Finally, areas that require additional study and attention regarding the usage of photocatalysts based on bismuth for removing pharmaceuticals and textile dyes from wastewater, particularly for real-world applications, are addressed.
Keywords: advanced oxidation processes; emerging contaminants; low-dimensional nanomaterials; pharmaceutical by-products; Schottky junction